Homicide in Criminal Law : A Research Companion - Reed, Alan; Bohlander, Michael; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
This volume presents a leading contribution to the substantive arena relating to homicide inthe criminal law. In broad terms, the ambit of homicide standardisations in extant law is contestable and opaque. This book provides a logical template to focus the debate. The overall concept addresses three specific elements within this arena, embracing an overarching synergy between them. This edifice engages in an examination of UK provisions, and in contrasting these provisions against alternative domestic jurisdictions as well as comparative contributions addressing a particularised research grid for content. The comparative chapters provide a wider background of how other legal systems treat a variety of specialised issues relating to homicide in the context of the criminal law.The debate in relation to homicide continues apace for academics, practitioners and within the criminal justice system. Having expert descriptions of the wider issues surrounding the particular discussion and of other legal systems approaches serves to stimulate and inform that debate. This collection will be a major source of reference for future discussion.
Introduction -- Part I -- 1: The Mandatory Sentence and the Case for Second Degree Murder -- - JEREMY HORDER -- 2: Killings Short of Murder: Examining Culpable Homicide in Scots Law - CLAIRE McDIARMID -- 3: Reforming English Homicide Law: Fair Labelling Questions and Comparative Answers? - ALAN REED AND MATT GIBSON -- 4: The Current State of Murder in English Law: A Critique, Wrong Turns and All - J.J. CHILD AND G.R. SULLIVAN -- 5: "Loss of Self Control" The Cultural Law of Sexual Infidelity and the Transformative Promise of the Fear Defence - SUSAN S. M. EDWARDS -- 6: Diminished Responsibility: A limited Partial Defence to Murder - RUDI FORTSON -- 7: Causing Death - SALLY KYD -- 8: The Termination of Pregnancy and the Criminal Law - JON HERRING -- 9: Homicide and the Vulnerable Subject of Criminal Law - CLAIRE DE THAN AND JESSE ELVIN -- 10: Recording Murder: Videos Depicting Homicide and the Law? - A.A.GILLESPIE -- Part II -- 11: South Africa - GERHARD KEMP -- 12: United States of America - VERA BERGELSON -- 13: Germany - KAI AMBOS AND STEPHANIE BOCK -- 14: New Zealand - JULIA TOLMIE -- 15: Netherlands - ERIC GRITTER -- 16: Turkey - R MURAT NOK -- 17: Islamic Law - MOHAMMAD HEDAYATI-KAKHKI -- 18: Sweden - MAGNUS ULVNG
Includes bibliographical references and index.
Also available in print format.
Keywords: LAW / Criminal Law / General; LAW / Criminal Law / Sentencing; Homicide -- Great Britain; Criminal law -- Great Britain; Criminal law; Homicide; Electronic books